NEW ECONOMIC CHALLENGES TO INTERNATIONAL BUSINESS DURING THE COVID-19 PANDEMIC - Divia Zulianti; Nuri Aslami (International Journal Labs, 2022)
The COVID-19 pandemic is currently engulfing the world, including Indonesia, causing various impacts including the economic sector, one of which has a major impact on the international business world. This study aims to determine the impact of the Covid-19 international economic and business challenges in Indonesia today. This type of research is a research with data analysis using qualitative methods. The results of the study show the impact of the Covid-19 pandemic on the global economy, including the international business economy. From the impact of this pandemic, the decline in demand for international products and the inhibition of production and export imports because the raw materials come from outside countries, the impact of this pandemic affects the realization of investment realization is hampered. No exception, investors who plan to invest in Islamic businesses. The increasing risk of Islamic financial institutions from this challenge international economic and business strategies can overcome the impact of the Covid-19 pandemic, it is hoped that international economic and business actors will show empathy and solidarity with stakeholders. international business people develop more profitable business strategies. International business players take advantage of and support the government's stimulus program. Banking and other financial institutions must start revising their growth targets, implementing digital transaction technology in one solution. The international economy and business can play a role in recovering from economic shocks by prioritizing the achievement of the objectives of the international business strategyImpact of Covid-19Impact of Covid-19Impact of Covid-19